2011
DOI: 10.1080/0144235x.2011.603237
|View full text |Cite
|
Sign up to set email alerts
|

Towards controlling molecular motions in fluorescence microscopy and optical trapping: a spatiotemporal approach

Abstract: This account reviews some recent studies pursued in our group on several control experiments with important applications in (one-photon) confocal and two-photon fluorescence laser-scanning microscopy and optical trapping with laser tweezers. We explore the simultaneous control of internal and external (i.e. centre-of-mass motion) degrees of freedom, which require the coupling of various control parameters to result in the spatiotemporal control. Of particular interest to us is the implementation of such contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 65 publications
(112 reference statements)
0
9
0
Order By: Relevance
“…In this sense, Dholakia group reported that trapping efficiency of 780 nm-sized silica bead (a particle in Lorenz-Mie regime) under 800 nm excitation is pulse-duration independent, 45 supporting the similar trapping efficiency of cwand fs-laser for 1.28 μm-sized particle. 30,46 A fascinating finding in such optical trapping with fs pulse train was axial ejection of 2.1-μm blue-fluorescent-dyed polystyrene bead from the trapping site almost immediately when it was immobilized by the incident laser above 15 mW. 45 Interestingly, the particle is trapped for up to a few minutes before an axial ejection only under laser power between 3.7 and 7 mW.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, Dholakia group reported that trapping efficiency of 780 nm-sized silica bead (a particle in Lorenz-Mie regime) under 800 nm excitation is pulse-duration independent, 45 supporting the similar trapping efficiency of cwand fs-laser for 1.28 μm-sized particle. 30,46 A fascinating finding in such optical trapping with fs pulse train was axial ejection of 2.1-μm blue-fluorescent-dyed polystyrene bead from the trapping site almost immediately when it was immobilized by the incident laser above 15 mW. 45 Interestingly, the particle is trapped for up to a few minutes before an axial ejection only under laser power between 3.7 and 7 mW.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This emphasizes that the trapping stability depends on peak power and pulse shape of the laser pulses . On the other hand, the role of low average power fs pulses at high repetition rate in stable optical trapping of dielectric nanoparticles less than 100 nm in diameter has been explained based on the inertial response time of the nanoparticles to the impulsive momentum transfer by laser pulses. , Though the axial ejection of the fluorescent bead at higher laser power may be a straightforward self-focusing effect under fs excitation which is opposite to an enhanced trapping efficiency under cw excitation, but the detailed explanation on such remarkable different phenomena of fs and cw mode in optical trapping of nanoparticle and microsized particles was still an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Although direct trapping of sub-micron objects, dimensionally, often similar to macromolecules, have been demonstrated using CW laser beam, it demands the use of quite high average powers. In our particular case where the particle dimension is at least an order of magnitude smaller than the wavelength of light, we are in the 'Rayleigh scattering limit' or the 'dipole limit' and under such condition, the trapping force is given by (1) where α is the polarizability and E is the electric field of trapping light. Since the force depends on the polarizability, earlier efforts revealed that much higher power levels are required to stably trap latex nanoparticles.…”
Section: Pulsed Optical Tweezersmentioning
confidence: 99%
“…This practical compromise, therefore, begets resolution enhancement as one of the most important developmental aspects of fluorescence microscopy. 1 Implementing multi-photon excitation in laser scanning microscopy for better depth resolution, for example, is an important achievement. However, in such two-photon fluorescence (TPF) microscopy, the broad spectral window of an ultrafast laser pulse and the overlapping multi-photon absorption spectra of common fluorophores lead to simultaneous excitation of many different fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…We have also explored the effect of different polarization states of the pulses used under such incoherent schemes, wherein their effect, as expected, is only minimal unlike in the coherent case. 1…”
Section: Introductionmentioning
confidence: 99%